Year in Review: Synopsis of Selected Articles in Neuroanesthesia and Neurocritical Care from 2018 - Rogan, Kyle J.; Chowdhury, Tumul; Venkatraghavan, Lakshmikumar (Journal of Neuroanaesthesiology and Critical Care, 2019)
This review is a synopsis of selected articles from neuroscience, neuroanesthesia, and neurocritical care from the year 2018 (January–October 2018). The journals reviewed included anesthesia journals, critical care medicine journals, neurosurgical journals as well as high-impact factor medical journals such as Lancet, Journal of American Medical Association (JAMA), New England Journal of Medicine (NEJM), and Stroke. This summary of important articles will serve to update the knowledge of anesthesiologists and other perioperative physicians who provide care to neurosurgical and neurocritical patients.
Keywords: literature review; neuroanesthesia; neurocritical care; randomized controlled trials